Preliminary Psychometric Evaluation of the Indonesian Version of the Aggression–Problem Behavior Frequency Scale (A-PBFS) in Adolescents - Mariskha, Silvia Eka (Fathana, 2026)
This study presents a preliminary psychometric evaluation of the Indonesian version of the Aggression–Problem Behavior Frequency Scale (A-PBFS) in adolescents. The aim was to examine the internal consistency and factorability of the scale as an initial step toward cultural adaptation in Indonesia. The sample consisted of 30 adolescents aged 12–17 years who met behavioral criteria related to aggression. The A-PBFS consists of 18 items measuring physical, non-physical, and relational aggression. Reliability was examined using Cronbach’s alpha, and construct factorability was assessed using the Kaiser–Meyer–Olkin (KMO) index and Bartlett’s test of sphericity. Despite the very small pilot sample (N = 30), the results showed excellent internal consistency (α = .947) and preliminary evidence of factorability (KMO = .782; Bartlett’s p < .001), indicating that the Indonesian version of the A-PBFS warrants further large-scale psychometric validation. Although a stable factor structure could not be established due to the limited sample size, these findings suggest that the Indonesian A-PBFS is a promising instrument for future large-scale psychometric validation.